Counterfactual thinking in patients with the behavioral variant of frontotemporal dementia (2024)
Social behavior and prosocial emotions are significantly compromised in behavioral variant frontotemporal dementia (bvFTD). Counterfactual thoughts (CT), which are mental representations of alternative outcomes to past events, play a pivotal role in regulating behavior and facilitating successful social interactions. This cognitive process relies on the prefrontal cortex and executive functions, both of which are compromised in bvFTD. Despite its importance, CT in bvFTD remains unexplored. This study aims to assess the production and characteristics of CT in bvFTD, Alzheimer's disease (AD), and healthy controls (HC). We enrolled 105 participants, including 38 patients meeting the revised criteria for probable bvFTD, 41 in the clinical control group with AD, and 26 in the healthy control group. The Montreal Cognitive Assessment and the Mini-Mental State Examination were administered to assess participants’ general cognitive function. We used the Spontaneous Counterfactual Generation Test, where participants recalled a negative event and described potential alternate outcomes, with their responses analyzed for frequency and type of CT (additive, subtractive, substitutional). The Counterfactual Inference Test further evaluated participants' ability to use CT to make inferences about different scenarios, scoring their responses to determine their alignment with normative patterns. In the Spontaneous Counterfactual Generation Test, significant differences in the number of counterfactual thoughts were found between groups, unrelated to age differences. HC and AD groups produced more CT than bvFTD patients, with HC generating significantly more than AD patients. The HC group excelled in producing additive, subtractive, and substitutional counterfactuals compared to the other groups, with the AD group outperforming bvFTD in additive and subtractive thoughts. The Counterfactual Inference Test revealed that after adjusting for age, AD patients and HC scored significantly higher than bvFTD patients, with no significant differences between AD and control scores. Our results suggest a marked impairment in CT abilities in bvFTD patients compared to both AD patients and healthy controls, reinforcing the potential of counterfactual thinking assessments as tools for differential diagnosis. Given the impact of CT on social behavior, these findings offer valuable insights for developing therapeutic interventions that leverage counterfactual thinking in social contexts for dementia patients.